Titanic [videorecording (DVD)] - Cameron, James, 1954-; DiCaprio, Leonardo; Winslet, Kate; Zane, Billy; Bates, Kathy, 1948-; Fisher, Frances, 1952- (2012)
A timeless love story born of tragedy that created an international phenomenon. This epic masterpiece is destined to sweep audiences anew into the journey of a lifetime.